Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1002/jpen.1532
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Fish Oil and Serum Fatty Acid Profiles in Pediatric Patients With Intestinal Failure–Associated Liver Disease

Abstract: Background: Intravenous fish oil (FO) treats pediatric intestinal failure associated liver disease (IFALD). There are concerns that a lipid emulsion composed of omega-3 fatty acids will cause an essential fatty acid deficiency (EFAD). This study’s objective was to quantify the risk for abnormal fatty acid concentrations in children treated with FO. Methods: Inclusion criteria for this prospective study was children with intestinal failure. Intravenous soybean oil (SO) was replaced with FO for no longer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(138 reference statements)
1
8
0
Order By: Relevance
“…Similar studies have confirmed these findings . This confirms that these patients did not develop EFAD, as they did not produce extra non‐EFAs to compensate for a decrease in ALA and LA concentrations …”
Section: Introductionsupporting
confidence: 86%
“…Similar studies have confirmed these findings . This confirms that these patients did not develop EFAD, as they did not produce extra non‐EFAs to compensate for a decrease in ALA and LA concentrations …”
Section: Introductionsupporting
confidence: 86%
“…An additional 2 papers were voted as important by a majority of the authors which allowed for a total of 6 papers to be identified for further evaluation. [7][8][9][10][11][12] An additional 9 articles comprising organizational guidelines, consensus, recommendation, and position papers included separately as important papers to our practice. [13][14][15][16][17][18][19][20][21] Of these 15 finalist articles, 6 were published in Journal of Parenteral and Enteral Nutrition, 6 in Clinical Nutrition, 2 in Journal of Trauma and Acute Care Surgery, and 1 in Nutrition in Clinical Practice.…”
Section: Resultsmentioning
confidence: 99%
“…Osowska et al 12 Effect of changing the lipid component of home parenteral nutrition in adults 5 Hartl et al 7 Calorie intake and short-term survival of critically ill patients 4* Ong et al 11 Intravenous Fish Oil and Serum Fatty Acid Profiles in Pediatric Patients with Intestinal Failure-Associated Liver Disease…”
Section: Resultsmentioning
confidence: 99%
“…There have been reports of FO‐ILE doses of up to 1.5 g/kg/day when additional calories are necessary and unable to be provided by higher dextrose loads 51 . Although FO contains minimal ALA and LA, patients receiving FO‐ILE at recommended doses have not developed clinical EFAD, because of DHA and EPA content within FO‐ILE 58 …”
Section: Prescribingmentioning
confidence: 99%